Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT. BPRS Al Salaam Amal Salman - Pebriansyah, Pebriansyah; Kurniawan, Prasetyo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Funding institutions are currently growing rapidly, leading to increased competition in the financial sector. To remain competitive, companies must ensure that employees can contribute effectively and achieve organizational targets. This study aims to examine the effect of leadership, motivation, and work environment on employee performance at PT. BPRS AlSalaam Amal Salman. The research uses a quantitative approach with a causal associative method. The population in this study consists of 81 employees, all of whom were selected using a census sampling technique. Data was collected using a questionnaire distributed via Google Forms through WhatsApp. The instrument used a Likert scale with five answer options. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The research involved descriptive analysis, classical assumption tests, and hypothesis testing. The results indicate that leadership, motivation, and work environment each have a positive and significant influence on employee performance. Furthermore, when tested simultaneously, these three variables reinforce each other in improving employee performance. The findings imply that organizations should focus on adopting effective leadership styles, fostering both intrinsic and extrinsic motivation, and creating a supportive work environment to enhance employee productivity and performance in a sustainable way.